2011
DOI: 10.1111/j.1708-8208.2011.00389.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective 10‐Year Cohort Study Based on a Randomized Controlled Trial (RCT) on Implant‐Supported Full‐Arch Maxillary Prostheses. Part 1: Sandblasted and Acid‐Etched Implants and Mucosal Tissue

Abstract: The implant survival was 95.1%. The mean value of bone loss after 10 years was 1.07 mm. Peri-implantitis were noted at the 5-year follow-up for one patient with a previous history of periodontitis; this patient did not attend the 10-year follow-up. This study shows that sandblasted and acid-etched implants offers predictable long-term results as support for full-arch maxillary prostheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
93
3
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(107 citation statements)
references
References 27 publications
(48 reference statements)
9
93
3
2
Order By: Relevance
“…(2017) performed a systematic review including papers with above 5‐year follow‐up yielding a 97.3% weighted implant survival rate. Numerous clinical studies with a 10‐year follow‐up yield survival rates of over 95% (Buser et al., 2012; Degidi, Nardi & Piattelli, 2012; Fischer & Stenberg, 2012; Gotfredsen, 2012; Jemt, 2017). For single tooth replacements on turned implants, cumulative survival rates of 96.8% after 17–19 years (Bergenblock, Andersson, Furst & Jemt, 2012) and 91.5% after 16–22 years (Dierens, Vandeweghe, Kisch, Nilner & De Bruyn, 2012) were reported.…”
Section: Introductionmentioning
confidence: 99%
“…(2017) performed a systematic review including papers with above 5‐year follow‐up yielding a 97.3% weighted implant survival rate. Numerous clinical studies with a 10‐year follow‐up yield survival rates of over 95% (Buser et al., 2012; Degidi, Nardi & Piattelli, 2012; Fischer & Stenberg, 2012; Gotfredsen, 2012; Jemt, 2017). For single tooth replacements on turned implants, cumulative survival rates of 96.8% after 17–19 years (Bergenblock, Andersson, Furst & Jemt, 2012) and 91.5% after 16–22 years (Dierens, Vandeweghe, Kisch, Nilner & De Bruyn, 2012) were reported.…”
Section: Introductionmentioning
confidence: 99%
“…119,150 A prospective RCT 10-year study on cast titanium-resin prostheses on 24 patients reported a total of 4.7 resin-related complications per prosthesis, which lingual gold onlays reduced. 151 Purcell et al, 152 in a retrospective chart review with an average recall time of almost 8 years, found that patients were 50 times more likely to replace posterior teeth at the 5-year mark than at the 2-year mark. The use of urethane dimethacrylate teeth has been suggested to reduce wear (SR Phonares NHC anterior, SR Phonares NHC posterior; Ivoclar Inc., Amhurst, NY).…”
Section: Maintenancementioning
confidence: 99%
“…Therefore, a number of studies has been reported on improving of implant body surface topography and chemistry for shortening the period of establish osseointegration, and increase the success rate of implant in these patients [2][3][4] . On the other hands, some studies were reported about methods of improving the jaw bone as host side.…”
Section: Introductionmentioning
confidence: 99%